Characterisation and optimisation of the d33 coefficient of cellular PP films. Issue 1 (1st January 2017) - Ortega Braña, Gustavo; Llovera‐Segovia, Pedro; Rodrigo Mor, Armando; Quijano, Alfredo
Abstract : Piezoelectric polymer cellular films have been studied since 1986. In recent years, they have improved the potential applications due to materials progress. Cellular polypropylene (PP) polymers are characterised by its high piezoelectric coefficient d 33 in comparison with other piezoelectric materials such as ceramics. One of the advantages of these films is their elasticity and flexibility. This study is based on the optimisation of the activation process and characterisation results of polymer cellular films. Samples were made of a commercially available PP film which was modified by a thermal biaxial stretching. Coefficient d 33 was measured by a quasi‐static method and the frequency characterisation was made for validating all characterisations and their relations. Transducer coefficients around 700 pC/N were obtained with polymer cellular PP films with silver coating electrodes, activated by corona discharge. An approximation of the surface charge density in the polymer voids was obtained with a mathematical model. Thermal stability was checked by thermally stimulated discharge currents (TSDCs) showing a relationship between the TSDC and the coefficient d 33 . Time stability was determined after 3000 h ageing, and finally was obtained a resonance frequency by interferometry measurement.